Survival Strategies and Coping Mechanisms of Syrian Female Head of Household in Egypt - Bahgat, Mirette (AUC Knowledge Fountain, 2015)
The objective of this research is to analyze the coping mechanisms that Syrian females head of household employ in Egypt in absence of survival strategies, and how different they are from the coping mechanisms employed by males head of household. The two questions I seek to answer through this research are : (1) What are the main challenges faced by Syrian female and male head of household in Egypt in five main areas: a. Safety and security b. Access to education c. Access to health services d. Social cohesion e. Access to economic opportunities and livelihoods (2) How do the coping mechanisms of Syrian female head of household differ from the male head of household in response to these challenges and the absence of survival strategies? My hypothesis is that in the absence of survival strategies, refugees resort to either positive or negative coping mechanisms as a response to challenges that face them in different areas of life. Female refugee head of household - often identified as one of the most vulnerable refugee groups- employ different coping mechanisms since they face gender-specific challenges than male head of household, a difference often ignored by academics, policy makers, and organizations providing services to the refugee community.